Literasi Kewirausahaan Sosial Islam Pada Pengusaha Muslim di Indonesia - Alifya Nurul Falach (Idarotuna : Journal of Administrative Science, 2023)
In emerging nations, there is an issue with the lack of entrepreneurs. Indonesia faces a number of difficulties, one of which is the dearth of Muslim businesspeople. Islamic entrepreneurship is frequently linked to moral and social values, which are actually ways that Muslims uphold the principles of their religion. This study makes an offer to provide a theoretical framework for encouraging Muslim businesspeople to engage in Islamic social entrepreneurship.